GRF-GIF Chimeras Boost Plant Regeneration. (March 2021) - Luo, Guangbin; Palmgren, Michael
Abstract : Low regeneration efficiency hampers plant transformation. Two independent studies demonstrate that GROWTH-REGULATING FACTORs (GRFs) alone or in chimeras with GRF-INTERACTING FACTOR (GIF) dramatically boost regeneration from tissue cultures from a broad range of species. GRF-GIF chimeras could be a game-changer in plant transformation and gene editing.